2022
DOI: 10.1186/s40945-022-00129-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of the painDETECT to discriminate musculoskeletal pain phenotypes

Abstract: Background Musculoskeletal pain patients present similar pain characteristics regardless of the clinical diagnosis. PainDETECT questionnaire is useful for screening neuropathic-like symptoms in many musculoskeletal conditions. However, no previous studies compared pain phenotypes of patients with musculoskeletal pain using the painDETECT. Therefore, the current study aimed to compare the pain characteristics of patients with musculoskeletal pain classified according to the painDETECT as nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…A pre-planned secondary analysis of data collected from a previous study by the present group of authors was undertook 23 . The original study was a cross-sectional observational study that followed the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) criteria (Atachment 1) 24 .…”
Section: Methodsmentioning
confidence: 99%
“…A pre-planned secondary analysis of data collected from a previous study by the present group of authors was undertook 23 . The original study was a cross-sectional observational study that followed the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) criteria (Atachment 1) 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Neuropathic pain leads to unfavourable outcomes and remains a major clinical challenge. People with neuropathic-like symptoms showed unfavourable pain features (i.e., pain intensity and functional limitation) compared to their counterparts [ 1 ]. Previous studies showed that neuropathic pain interferes with several aspects of an individual’s life, such as poor sleep quality [ 2 ], physical impairment [ 3 ], and a large psychosocial burden [ 4 ].…”
Section: Introductionmentioning
confidence: 99%